STUDI PERBANDINGAN OPTIMALISASI INDUSTRI HALAL DALAM PEMBANGUNAN EKONOMI INDONESIA DAN MALAYSIA - Asmaria, Asmaria (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to analyze the comparison optimization of the halal industry in the economic development of Indonesia and Malaysia. The research was conducted in 2 countries, by reviewing and analyzing the optimization the halal industry in the economic development of Indonesia and Malaysia. This research uses primary data and secondary data which are primary data; interviews with key informants and secondary data; use study documentation and literature study. The growth of the Malaysian and Indonesian halal industries is expected to continue. According to Islamic law, one of the main principles of Sharia is the maintenance of life in a manner sustainable to match economic development. Having these criteria can help provide guidance to halal certification bodies such as JAKIM and BPJPH in implementing halal product certification in Malaysia and Indonesia. In addition, pharmaceutical products for halal consideration must follow the laws and requirements imposed by the legal or competent authorities in Malaysia and Indonesia.